Physio-Biochemical Characteristics of Prope Legitimate Seedlings of 13 Cocoa Clones Under Drought Stress - Zasari, Maera; Wachjar, Ade; Susilo, Agung Wahyu; Sudarsono, Sudarsono (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2023)
The tolerant seedlings are determined by their physiological and biochemical responses. This study aimed to determine stomatal density, relative water content, and proline in prope legitimate seedlings under drought stress. The research was carried out at the Indonesian Coffee and Cocoa Research Center in July 2018 – February 2019, arranged in a randomized split-plot experimental design with six replications. The main plot was soil moisture content, and the sub-plot was the cocoa prope legitimate seedlings. The differences of mean values were tested using analysis of variance, followed by the DMRT and T-student test at 5 % level, analysis of the relative decrease in stomatal density and relative water content, proline content ratio, and the dendrogram analysis. The results showed that the cocoa seedlings under drought experienced significant changes in relative water and proline content but not stomatal density. Drought decreased in the relative water content of 50% and increased proline content in the seedlings. The relative water and proline content divided the prope legitimate seedlings into two groups. The prope legitimate seedlings from KW 516, KW 641, Scavina 06, KKM 22, KW 617, and ICCRI 03 clones were drought-tolerant.